Magneto-optical and microstructural properties of spinel cubic copper ferrites with Li-Al co-substitution. Issue 12 (15th August 2018) - Slimani, Y.; Güngüneş, H.; Nawaz, M.; Manikandan, A.; El Sayed, H.S.; Almessiere, M.A.; Sözeri, H.; Shirsath, S.E.; Ercan, I.; Baykal, A.
Abstract: Nanospinel Li2x Cu1-x Aly Fe2-y O4 ferrites with composition x = y = 0.0, 0.2, 0.3 and 0.4, were successfully synthesized via hydrothermal method. The effect of co-substitution (Li and Al) on structural, morphological and magnetic properties of CuFe2 O4 nanoparticles were investigated using Powder X-ray Diffraction (XRD), Fourier-Transform Infrared spectroscopy (FT-IR), Scanning Electron Microscopy (SEM), Vibrating Sample Magnetometer (VSM) and Mossbauer spectroscopic techniques. The cation distribution of all composition was calculated. Both XRD and FT-IR analyses confirmed the synthesis of single-phase spinel cubic product for all the substitutions. Mossbauer investigation showed that the Li 1+ and Al 3+ ions occupied B-sites. Nonetheless, some amounts of Li 1+ occupy A-site. The magnetization hysteresis loops M (H), revealed that the final products with x, y = 0.0, 0.3 and 0.4 exhibit superparamagnetic (SPM) behavior at room temperature, however the composition x, y = 0.2 displays a ferromagnetic-like (FM) behavior. The saturation magnetization (Ms ) reduces with rising the Li and Al contents. Compared to pristine CuFe2 O4 spinel, the remanent magnetization (Mr ), coercive field (Hc ) and the magneto-crystalline anisotropy fields (Ha ) improved for products synthesized with x, y = 0.2 and then decrease for x, y = 0.3 and 0.4. The squareness ratio Mr /Ms are less than 0.500, which suggest the single domain nanoparticles with uniaxial anisotropy for Li2x Cu1–x Aly Fe2-y O4 (0.0 ≤ x, y ≤ 0.4) nanoparticles. The magneto-crystalline anisotropy constant (Keff ) value is improved for Li0.8 Cu0.6 Al0.2 Fe1.8 O4 (i.e. x, y = 0.2) magnetic nanoparticles and then decreased for higher Li and Al contents, due to the replacement of Cu and Fe ions with respectively Li and Al ions.